A Study Of The Ability Of Altman's Z Score Model In Predicting Financial Distress For Malaysian Firms - Wei, Chong Chin (2000)
This paper attempts to test the ability of Altman's Z Score model in prediacting financial distress firms in the Malaysian context by using the profile of past financial performance of those selected failed and non-failed listed companies on KLSE.